The role of chemerin and chemerin receptors during acute inflammation - Valaris, S (2017)
Cytokines play a major role in orchestrating the inflammatory process. This thesis focuses on one such cytokine, called chemerin. Chemerin is a multifunctional protein that is secreted as an inactive precursor, prochemerin, which becomes proteolytically cleaved at the C-terminus into the active signalling molecule, chemerin. Chemerin binds three G-protein coupled receptors: ChemR23, GPR1 and CCRL2, and acts as a chemoattractant, primarily via the ChemR23 receptor expressed on immature dendritic cells, natural killer cells and macrophages. The role of chemerin during inflammation remains controversial. However, multiple studies have reported elevated levels of chemerin in patients suffering from a plethora of inflammatory and metabolic diseases. The need for proteolytic cleavage of chemerin's inactive precursor, prochemerin, results in a myriad of prochemerin-derived isoforms, with varying signalling ability. Current commercially available antibodies are not able to detect different different chemerin isoforms. Therefore, one of the aims of my work was to develop and characterise anti-chemerin antibodies derived from a naive phage display library, which could recognise the inactive sequence of prochemerin and the C-terminus of active chemerin. I set out to investigate the role of chemerin receptors during early stages of inflammation in a well-established model of acute inflammation. Prior to this, I surveyed the protein and mRNA expression of the ChemR23 receptor and the mRNA expression of CCRL2 and GPR1 chemerin receptors on leukocyte subsets. Following this, I investigated the role of the non-signalling chemerin receptor, CCRL2, using an acute inflammatory model of zymosan-induced peritonitis. Mice lacking the CCRL2 receptor displayed augmented inflammatory response compared to age-matched wild type mice. In early time points of this inflammatory model, the CCRL2 knockout mice displayed increased neutrophil and monocyte infiltration to the site of inflammation and augmented mediator production of CXCL1 partly caused by the increased levels of chemerin in the knockout mice. The use of a neutralising chemerin antibody and the pre-treatment of excess recombinant chemerin led me to this conclusion. These pro-inflammatory effects of chemerin were mediated via signalling through the ChemR23 receptor. ChemR23 deficient mice display a reduction in neutrophil and monocyte recruitment to the site of inflammation in the same early time points of zymosan-induced peritonitis. The final aim of this thesis was to investigated the behavioural phenotype of CCRL2 deficient mice after 3 years of working with them. Mice lacking the CCRL2 receptor exhibited increased anxiety behaviour under steady state conditions. Immunohistochemistry of their neuroanatomy showed no differences from age-matched wild type mice. However, wild type in vitro cultured microglia cells express the chemerin receptors. Taken together the results from this thesis illustrate the pro-inflammatory effects of chemerin in early stages of inflammation. Furthermore, the non-signalling chemerin receptor CCRL2 plays a non-redundant role in dampening the effects of chemerin in early stages of inflammation. Further research should be undertaken to elucidate chemerin's role during chronic disease setting of inflammation, in order to suggest whether chemerin could be a beneficial therapeutic target against human disease.